Quando a cultura entra na moda: a mercadologização do artesanato e suas repercussões no cotidiano de bordadeiras de Maranguape - Silva, Emanuelle Kelly Ribeiro da (2009)
This study wants to understand the relationships involving the interference of public policy programs in the handcraft by the role played by fashion designers in the production process of artisans in order to adjust the handcraft product to market needs by observing groups of embroiderers located in Maranguape. In addition to describing the consequences that this new reality gives the daily lives of artisans, creating many changes in their lifestyle and the way they value the product of their work, this study is also permeated by social and cultural factors that influencing the creation of demand for handcraft products at present time, the need for adding value commercial to industrial goods, the need to distinguish between social groups and income generation for people who are outside the system of industrial production.